I Ended up, by ANother Way, Reaching the Sea (2011)
This article give voice to José Ignacio Martínez, professor at Universidad EAFIT: "I applied to two undergraduate programs: Marine Biology and Geology. I moved on to both, but I chose Geology considering my dad's resources, because even though he worked at the Bank of the Republic and they paid up to 60% of the education, Marine Biology required a time in Cartagena. Now I work with marine microphosils; I ended up, by another way, reaching the sea."